Exploring skill requirements for the industry 4.0: A worker-oriented approach - Peña-Jimenez, Marco; Battistelli, Adalgisa; Odoardi, Carlo; Antino, Mirko (Anales de Psicología / Annals of Psychology, 2021)
Emerging technologies are shaping the world of work, thus creating an increasingly digital industry, also known as “Industry 4.0”. Thus, examining skill requirements becomes essential to facilitate organizational adaptation to this technological revolution. The aim of this study was to explore the perception of skill requirements of workers of a highly technological manufacturing company. In Study 1 (n = 671), an exploratory factor analysis was carried out to identify relevant groups of skills. A year later, in Study 2 (n = 176), we confirmed the factor structure through a confirmatory factor analysis and we conducted a latent growth curve analysis to examine potential changes of the previous skill requirements due to the lockdown and the forced remote working during the COVID-19 pandemic. Findings showed that cognitive, functional business, strategic and managing people skills are considered as important resources for the industry 4.0, being the functional business skills increasingly relevant in time 2. Moreover, we identified differences between managers and subordinates regarding such skills. We discuss theoretical and practical implications for skills development in the digital age.